Long-Term Outcomes and Exploratory Analyses of the Randomized Phase III BILCAP Study. Issue 18 (20th June 2022) - Bridgewater, John; Fletcher, Peter; Palmer, Daniel H.; Malik, Hassan Z.; Prasad, Raj; Mirza, Darius; Anthony, Alan; Corrie, Pippa; Falk, Stephen; Finch-Jones, Meg; Wasan, Harpreet; Ross, Paul; et al.
Abstract : PURPOSE: The BILCAP study described a modest benefit for capecitabine as adjuvant therapy for curatively resected biliary tract cancer (BTC), and capecitabine has become the standard of care. We present the long-term data and novel exploratory subgroup analyses. METHODS: This randomized, controlled, multicenter, phase III study recruited patients age 18 years or older with histologically confirmed cholangiocarcinoma or muscle-invasive gallbladder cancer after resection with curative intent and an Eastern Cooperative Oncology Group performance status of < 2. Patients were randomly assigned 1:1 to receive oral capecitabine (1, 250 mg/m 2 twice daily on days 1-14 of a 21-day cycle, for eight cycles) or observation. The primary outcome was overall survival (OS). This study is registered with EudraCT 2005-003318-13. RESULTS: Between March 15, 2006, and December 4, 2014, 447 patients were enrolled; 223 patients with BTC resected with curative intent were randomly assigned to the capecitabine group and 224 to the observation group. At the data cutoff of January 21, 2021, the median follow-up for all patients was 106 months (95% CI, 98 to 108). In the intention-to-treat analysis, the median OS was 49.6 months (95% CI, 35.1 to 59.1) in the capecitabine group compared with 36.1 months (95% CI, 29.7 to 44.2) in the observation group (adjusted hazard ratio 0.84; 95% CI, 0.67 to 1.06). In a protocol-specified sensitivity analysis, adjusting for minimization factors, nodal status, grade, and sex, the OS hazard ratio was 0.74 (95% CI, 0.59 to 0.94). We further describe the prognostic impact of R status, grade, nodal status, and sex. CONCLUSION: This long-term analysis supports the previous analysis, suggesting that capecitabine can improve OS in patients with resected BTC when used as adjuvant chemotherapy after surgery and should be considered as the standard of care.